Lagging in the Interior Village (Study of Government Participation in Community Development in Pariangan Village, Polewali Mandar Regency) - Adrianah Adrianah; Asniwati Asniwati; Yusra Nginang (Jurnal Office, 2021)
This study aims to find out the shape of the backwardness of inland Villages in Luyo Sub-district Polewali Mandar District and GoVernment Participation in the existing development in Kecamatan Luyo Polewali Mandar Regency.  This type of research is qualitative.  Research  Sites  in  Kecamatan  Luyo Polewali      Mandar      District.      Determination or retrieval of informant/respondent in this research by purposive sampling,  as many as 7 people with a background as goVernment apparatus and society. Data collection techniques are done by observation,   interView, and documentation with the following data: 1. Primary data, 2. Secondary data, and analyzed by using descriptive analysis technique (general, summarizing the Various signals, moVement, or real social phenomenon). The results of this research are 1. The Form of Backwardness of Inner Village in Luyo Sub-district Polewali Mandar Regency. The Village is still categorized as a  lagging  Village.  2.  Government  participation  in  the  development  and community participation to build inland areas